2021
DOI: 10.1002/jpln.202100056
|View full text |Cite
|
Sign up to set email alerts
|

FTIR spectral band shifts explained by OM–cation interactions

Abstract: Background: The organic matter (OM) in soils interacts with polyvalent cations such as Ca2+ through hydroxyl (OH), carboxylic acid, ester, keto, aldehyde (summarized as C=O), and carboxylate (COO−) functional groups. Such interactions affect the bonding strength of the double bond between the C and the O atom in the functional groups, which is assumed to shift the wavenumber (WN) region of O–H (hydroxyl), C=O, COO−, and OMcat (i.e., C=O interacting with cations plus O–H groups) absorption band maxima in the Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 26 publications
5
21
0
Order By: Relevance
“…Many studies investigated in detail the relationship between diffuse reflectance spectra and soil properties from underlying chemical perspective (e.g., Bornemann et al., 2010; Ellerbrock & Gerke, 2021). Nevertheless, practical application in lab routine analyses or in field studies is still subjected to methodological restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies investigated in detail the relationship between diffuse reflectance spectra and soil properties from underlying chemical perspective (e.g., Bornemann et al., 2010; Ellerbrock & Gerke, 2021). Nevertheless, practical application in lab routine analyses or in field studies is still subjected to methodological restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…In the research by R. H. Ellerbrock et al, the interaction between Ca 2+ and carboxyl groups of polygalacturonic acid (PGA) molecule was studied by FTIR, and it was revealed that the addition of Ca 2+ to PGA causes the formation of COO− groups, resulting in an increased intensity of COO− absorption and decreased intensity of COOH band. It was also observed that C=O and COO− absorption bands were shifted toward the lower wavenumbers ( Ellerbrock and Gerke, 2021 ). However, as sodium hyaluronate is used within this study, the COO- group is already formed in the HA molecule and the intensity change of C=O and COO− groups upon the addition of Ca 2+ are difficult to determine.…”
Section: Resultsmentioning
confidence: 98%
“…However, the concentration of aromatic compounds determined by FTIR was poorly correlated with the C/N ratio (R = −0.004), and thus there was a weak relationship between the NMR and FTIR (R = 0.018) aromatic fractions. This could have been due to band shifts in the FTIR spectra resulting from interaction of OM with polyvalent cations, which is suggested to shift the wavenumber region of functional groups [54,55].…”
Section: Structural Composition and Functional Groupsmentioning
confidence: 99%